Planning and execution of sustainable practices on construction sites (Research, Society and Development, 2024)
This article addresses sustainability in the Brazilian construction industry, focusing on waste management and sustainable practices. The general objective of this project is to evaluate the applicability of strategic environmental management planning in a construction company located in Barra do Piraí - State of Rio de Janeiro (RJ). environmental aspects, as well as reducing resource consumption as essential measures to promote sustainability in the construction sector. The research was carried out through a case study and the methodology adopted was qualitative and observational for data collection. the need to implement sustainable practices on construction sites to promote benefits such as: acquisition of certifications, national recognition, reduction of environmental and social impacts. As a result of the assessment of environmental impacts, the physical environment showed non-conformities for the air and this is due to. noise pollution and poor air quality, and for the biotic environment it was observed that 75% of the evaluated items presented non-conformities for the interference of the construction site related to local fauna and flora, in addition to the local ecosystem. A study of the PDCA cycle for the Biotic environment was necessary as suggestions to be adopted to increase compliance and a SWOT analysis was carried out to highlight strengths and weaknesses. The main weakness is the final disposal of waste and the strong point is the planned infrastructure of the construction site.